Remote coaching system for runner's form with wearable wireless sensor. (1st January 2011) - Gotoda, Naka; Matsuura, Kenji; Otsuka, Shinji; Tanaka, Toshio; Yano, Yoneo
This paper describes a remote training which supports the coaching of runner's form by applying wearable wireless sensors. The system provides a trainer with kinematic information about exercise behaviour of a trainee through monitoring the arm swing with the tri-axial accelerometer in real time. While a trainer can advise the improvement of body movement on a web browser, a trainee can receive the indication during running as a sound feedback. We have designed and implemented our proposal. From the result of an experiment, it was found that the system contributed to the stabilisation of the running form through trainer's appropriate advice.